Impact of focused ion beam on structural and compositional analysis of interfaces fabricated by surface activated bonding. (26th November 2019) - Ohno, Yutaka; Yoshida, Hideto; Kamiuchi, Naoto; Aso, Ryotaro; Takeda, Seiji; Shimizu, Yasuo; Nagai, Yasuyoshi; Liang, Jianbo; Shigekawa, Naoteru
Abstract: We have shown that the structural and compositional properties of semiconductor interfaces fabricated by surface activated bonding (SAB) would be modified during focused ion beam (FIB) processes operated at room temperature (RT), especially for wide band-gap materials, and such a modification can be suppressed by FIB processes operated at lower temperatures. During FIB processes operated at RT, SAB-fabricated Si/Si and GaAs/GaAs interfaces are amorphized along the interfaces, even at the internal locations deeper than the penetration depth of the FIB, and the impurity distribution across the interfaces is modified. This phenomenon is presumably due to the atomic diffusion assisted by the point defects that are introduced by FIB irradiation. By using FIB processes operated at −150 °C, the FIB-induced atomic diffusion would be ignored for Si/Si interfaces. Meanwhile, the diffusion would be still effective for GaAs/GaAs interfaces, presumably due to the effects of recombination-enhanced defect motion under FIB irradiation.